Familial isolated congenital asplenia: case report and literature review. - Ahmed, SA; Zengeya, S; Kini, U; Pollard, A (2010)
Congenital asplenia is a rare life-threatening condition, often presenting with pneumococcal sepsis. It may arise as part of situs abnormalities or result from an unrelated specific defect of spleen development. The mode of inheritance is usually autosomal dominant, though sporadic cases are also reported. In affected individuals, the use of appropriate antibiotic prophylaxis and immunisations could save lives. In our report, we describe a family of three siblings with isolated congenital asplenia and unaffected parents, suggestive of recessive inheritance. The diagnosis in the proband was made post mortem following overwhelming pneumococcal sepsis. We also review the literature and compare the eight families previously reported with congenital isolated asplenia.